Quantitative Assessment of Forest Site Productivity - Shrivastava, M. B.; Ulrich, B. (Indian Forester, 1978)
The aim of this study was to develop methods of deriving quantitative site parameters from qualitative site descriptions and to se1ect the parameters best adapted to assess quantitatively the top height growth of Norway Spruce in the hilly region of Hesse. In total 220 site parameters were defined by using different approaches to express the growth factors 44 paramelers explained 97.37% of variation in tree height at age 80. By reasonab1e selection of site parameters, >80% of the variations were explained with 20 parameters where as about 10 parameters explained >700% of the height variation. Stratification of sites according to the geological formation increased the precision of estimates. On account of intercorrelation of site parameters with each other, the forecast about the relative importance of different growth factors for Spruce can be made with reservation. If one recognizes the partial measure of determination (R2) as a scale in the multiple regression of parameters with tree height, then the soil water supply has the greatest importance folJowed by nutrient supplies among which nitrogen stands first. If reasonable care is taken to avoid mensurational errors and growth variations caused by biological factors, error of individual estimates within the sample population usually approaches maximum up to 10% of the observed total height.